Mid-upper arm circumference only protocol in Pakistan: missed opportunities for children suffering from severe acute malnutrition? A mixed-methods observational study - Benjamin Guesdon; Meena Iqbal Faruqi; Muhammad Ilyas Siddiqui; Gulzar Usman; Kanwal Naz Ariser; Rafaina Shah; Fatima Amin; Muntaha Masoud; Qamar Din Tagar; Brigitte Tonon; Elise Lesieur; Khalida Naz Memon (Cambridge University Press, 2024)
Abstract Objective: We investigated the missed treatment opportunities affecting programmes using mid-upper arm circumference (MUAC) as the sole anthropometric criterion for identification and monitoring of children suffering from severe acute malnutrition (SAM). Design: Alongside MUAC, we assessed weight-for-height Z-score (WHZ) in children screened and treated according to the national MUAC only protocol in Pakistan. Besides, we collected parents' perceptions regarding the treatment received by their children through qualitative interviews. Setting: Data were collected from October to December 2021 in Tando Allah Yar District, Sindh. Subjects: All children screened in the health facilities (n 8818) and all those discharged as recovered (n 686), throughout the district, contributed to the study. All children screened in the community in the catchment areas of five selected health facilities also contributed (n 8459). Parents of forty-one children randomly selected from these same facilities participated in the interviews. Results: Overall, 80·3 % of the SAM cases identified during community screening and 64·1 % of those identified in the health facilities presented a 'WHZ-only' diagnosis. These figures reached 93·9 % and 84·5 %, respectively, in children aged over 24 months. Among children treated for SAM and discharged as recovered, 25·3 % were still severely wasted according to WHZ. While parents positively appraised the treatment received by their children, they also recommended to extend eligibility to other malnourished children in their neighbourhood. Conclusion: In this context, using MUAC as the sole anthropometric criterion for treatment decisions (referral, admission and discharge) resulted in a large number of missed opportunities for children in need of timely and adequate care.